2019
DOI: 10.1108/jcre-01-2019-0003
|View full text |Cite
|
Sign up to set email alerts
|

From needs to deeds

Abstract: Purpose This paper aims to study a change process on a university campus from a pedagogical perspective. The aim of the process, as expressed by facilities management and faculty leadership, was to create campus learning landscapes that promote social encounters and learning between students and researchers, as well as other embedded groups. The paper addresses how pedagogical needs are or should be integrated in the design process. Design/methodology/approach The data of this case study regarding change on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(23 citation statements)
references
References 40 publications
0
18
0
Order By: Relevance
“…Qualitative goals . We found that Häne (2020), Backhouse (2019), Sandström and Nevgi, (2020), Van Marrewijk and Van den Ende (2018), Vitasovich (2016), Van Sprang (2012), Pinder (2009) and Van der Voordt and Van der Klooster (2008) reflected upon whether the qualitative goals (increased productivity, collaboration and knowledge-sharing, for example) had been met. For instance, Van der Voordt and Van der Klooster (2008) reflected upon the intended goals of interaction and collaboration and concluded that ABW had not met these aims.…”
Section: Resultsmentioning
confidence: 93%
See 4 more Smart Citations
“…Qualitative goals . We found that Häne (2020), Backhouse (2019), Sandström and Nevgi, (2020), Van Marrewijk and Van den Ende (2018), Vitasovich (2016), Van Sprang (2012), Pinder (2009) and Van der Voordt and Van der Klooster (2008) reflected upon whether the qualitative goals (increased productivity, collaboration and knowledge-sharing, for example) had been met. For instance, Van der Voordt and Van der Klooster (2008) reflected upon the intended goals of interaction and collaboration and concluded that ABW had not met these aims.…”
Section: Resultsmentioning
confidence: 93%
“…increased student-teacher distance in time and space (Baldry and Barnes, 2012; Van Marrewijk and Van den Ende, 2018; Sandström and Nevgi, 2020; Nooij et al , 2022); and…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations